2011
DOI: 10.1007/s00262-011-1154-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the evolution of immune phenotype during the development and progression of squamous cell carcinoma of the head and neck

Abstract: While studies have indicated that squamous cell carcinoma of the head and neck (HNSCC) is associated with immune suppression, these studies did not analyze the immune response at the dysplastic stage. The present study utilized a mouse model of 4-nitroquinoline 1-oxide-induced oral carcinogenesis to examine the alterations in immune phenotype at the premalignant and malignant stages of HNSCC. Cervical lymph nodes of HNSCC-bearing mice were found to contain a greater number of cells, including a greater number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 33 publications
(46 reference statements)
3
77
0
Order By: Relevance
“…This model represents the stages of carcinogenesis‐induced cancer described for tobacco products 41. In addition, similar to what has been shown for human subjects with premalignant lesions, we had previously shown that mice bearing 4NQO‐induced premalignant oral lesions have increased expression of PD‐1 on their CD4 + and CD8 + T‐cells 8. The results of this study showed an early increase in spleen cell secretion of the Th1 cytokine IL‐2 and the inflammatory cytokines IL‐6, IL‐17 and TNF‐α after one week of treatment with antibody against PD‐1, and an increase of IFN‐γ after 3 weeks of treatment.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This model represents the stages of carcinogenesis‐induced cancer described for tobacco products 41. In addition, similar to what has been shown for human subjects with premalignant lesions, we had previously shown that mice bearing 4NQO‐induced premalignant oral lesions have increased expression of PD‐1 on their CD4 + and CD8 + T‐cells 8. The results of this study showed an early increase in spleen cell secretion of the Th1 cytokine IL‐2 and the inflammatory cytokines IL‐6, IL‐17 and TNF‐α after one week of treatment with antibody against PD‐1, and an increase of IFN‐γ after 3 weeks of treatment.…”
Section: Discussionsupporting
confidence: 67%
“…The identity of these premalignant oral lesions and HNSCC was confirmed histologically. Clinical assessments of lesions were quantitated in a blinded manner by counting the number of visible lesions, and giving lesions a gross pathologic score between 1 and 4 based on their horizontal and vertical size, and overall appearance 8. The following criteria were used for scoring: 1: flat macule, 2: raised papule, 3: raised plaque, 4: grossly exophytic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have indicated that HNSCC is associated with immune suppression and this could explain the high reoccurrence rate of this type of cancer. 4 Malignant HNSCC cells may escape immune surveillance by different strategies: they can avoid immune recognition or they may affect immune system efficiency. For instance, recognition of tumor cell is hampered by the significant decrease of antigen-presenting cells and their effectiveness.…”
Section: Hnscc and Immune Escapementioning
confidence: 99%
“…These data are sustained by studies in a murine model of 4-nitroquinoline-1-oxide induced oral carcinogenesis, where the progression from premalignant lesion to oral squamous cell carcinoma (OSCC) was characterized by a progressive increase of Th17 cells and IL-17. 4,31 How Th17 cells increase may be a favorable factor in tumor progression is still a matter of debate; nevertheless, one convincing hypothesis is that Th17 cells might have a significant role in promoting intra-tumor angiogenesis. 29 IL-17 steadily increases during HNSCC progression.…”
Section: T-helper Cells and Hnscc Development T-helper (Th) Lymphocytmentioning
confidence: 99%